New records and an updated checklist of the Stoneflies (Plecoptera) from Florida - Ray, Donald H. (Illiesia, 2012)
New state records of Allocapnia starki Kondratieff & Kirchner, Isogenoides varians (Walsh), and Perlesta shubuta Stark are presented for Florida. Ecological notes for Florida populations and additional new collection records for Alloperla prognoides Surdick & Stark and several other stonefly species are presented. Larvae and adults were collected in or along gravel stream reaches.
Keywords: Allocapnia; entomology; Alloperla; Isogenoides; Perlesta; Florida